2021
DOI: 10.1111/1346-8138.15913
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of psoriasis: A review

Abstract: Psoriasis is a complex chronic inflammatory skin disease caused by the dynamic interplay between multiple genetic risk foci, environmental risk factors, and excessive immunological abnormalities. Psoriasis affects approximately 2% of the population worldwide, and dramatic advances have been achieved in the understanding and treatment options for psoriasis. Recent progress in biological therapies has revealed the fundamental roles of tumor necrosis factor‐α, interleukin (IL)‐23p19, and the IL‐17A axis together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 83 publications
1
50
0
3
Order By: Relevance
“…Therefore, it may drive an amplifying loop from IL-23 to IL-17 to IL-36γ and back again to IL-23, thus maintaining the diseased state. All of these cytokines are elevated in psoriasis skin lesions, and correspondingly neutralizing TNF, IL-23 p19, or IL-17A has shown strong therapeutic benefit in patients with psoriasis ( 2 , 8 , 9 ). Although these current treatments have proven efficacy, some patients fail to respond, they become resistant to therapy over time, or their disease comes back when treatment is stopped.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may drive an amplifying loop from IL-23 to IL-17 to IL-36γ and back again to IL-23, thus maintaining the diseased state. All of these cytokines are elevated in psoriasis skin lesions, and correspondingly neutralizing TNF, IL-23 p19, or IL-17A has shown strong therapeutic benefit in patients with psoriasis ( 2 , 8 , 9 ). Although these current treatments have proven efficacy, some patients fail to respond, they become resistant to therapy over time, or their disease comes back when treatment is stopped.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines promote the differentiation of naïve T cells into Th1, Th22, and Th17 cells [3]. IL-17, mainly secreted by Th17 cells, causes abnormal proliferation of keratinocytes and stimulates them to release various chemokines [9], thereby resulting in the formation of classic psoriatic plaques. However, recent articles suggest a role of Th17 cells in anti-ACR-positive myasthenia gravis [5], The suggested mechanism of thymic inflammation involves dysregulation of interferon type I pathway which leads to overexpression of IL-23 and thus to overproduction of IL-17 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is an immune-mediated chronic inflammatory skin disease, in which intralesional T lymphocytes and their proinflammatory signals trigger keratinocytes to rapidly proliferate and initiate the inflammatory process ( 1 ). Previous studies reported that the IL-23/T helper (Th)17 axis played a crucial role in the pathogenesis of psoriasis ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%